UNRAVELING THE MENTAL WORKLOAD OF EMPLOYEES: A CONTEMPORARY APPROACH IN PT WOM FINANCE CAB PAREPARE - Kulsaputro, Januar; Pawennari, Andi; Safutra, Nur Ihwan; P, A Dwi Wahyuni; Dahlan, Muhammad (Center for Study and Journal Management FTI UMI, 2024)
A company's success depends on effective resource management, particularly human resources. Utilizing high-quality employees is crucial for achieving goals, optimizing efficiency, and enhancing performance. However, workloads often cause stress and fatigue, impacting accuracy and job satisfaction. Therefore, measuring mental workload is important, using techniques like the Subjective Workload Assessment Technique (SWAT) to understand employee workload and improve performance. This study focuses on PT. Wom Finance, a vehicle financing company, and its efforts to address workload challenges using SWAT to measure and enhance employee satisfaction. The research reveals that effort (35.78%), stress load (34.29%), and time load (29.94%) are significant factors in the overall workload. Further research is recommended to deepen understanding and develop strategies for reducing workload. By effectively managing employees' mental workload, PT WOM Finance Cab Parepare can create a work environment that promotes satisfaction and well-being, leading to increased productivity and organizational success.